Perceived outcomes of online parenting information according to self‐selected participants from a population of website users. Issue 1 (2015) - Pluye, Pierre; Sherif, Reem El; Bartlett, Gillian; Granikov, Vera; Grad, Roland M; Doray, Geneviève; Lagarde, François; Loignon, Christine; Bouthillier, France
ABSTRACT: Looking for consumer health/well‐being information online is increasingly common. However, little is known about how people are using information targeted to a specific audience, and what happens as a result of this use. We partnered with 'Naitre & Grandir' (N&G), a magazine, website and newsletter offering trustworthy parenting information on child growth, development and health/well‐being. This study was designed to uncover the outcomes of online parenting information. We used the theory‐driven Information Assessment Method (IAM) to study parental perceptions regarding outcomes of specific N&G web pages. A research question was: Is there a difference between parents with a low level of education and income vs. other parents? Over an 8‐month study period, 4007 participants submitted 4862 IAM ratings that suggested N&G information was valuable in terms of situational relevance (93.7%), positive cognitive impact (92.9%), intention to use (85.7%), and expectation for child health/well‐being benefit (82.4%). In addition, results suggested participants with a low level of education and income were more likely to (i) seek and use information for the child of someone else, and (ii) expect being more engaged in decision‐making for their child, and being less worried regarding a problem concerning their child. Our results do not support an association between the combined level of income and education, and perceived outcomes of information. This is the first study to assess outcomes of emailed parenting information from a parental viewpoint. More research is needed to better understand outcomes of targeted online information, which may ultimately contribute to improve people's health/well‐being.